The genetics of general knowledge: a twin study from Croatia - Bratko, Denis (Array, 2010)
The purpose of this study was to explore genetic and environmental influences on general knowledge (GK) and its relationship with intelligence. The sample consisted of 71 MZ and 78 DZ twin pairs, aged on average 17 years. General knowledge was measured with a test consisting of 60 items measuring different domains of GK including geography, history, politics, art, science, fashion, and sport. Four different measures of intelligence were used, two that measured spatial abilities (visualization and spatial orientation) and two that measured verbal abilities (word fluency and vocabulary). Univariate analyses indicated that the heritability of GK is .87, while heritability estimates for cognitive ability measures ranged from .48 to .73. Bivariate analyses between each of the four intelligence measures and GK measure were carried out using correlated factors model. Shared genetic influences were found between GK and all four intelligence measures in the .40–.80 range.